The data management study of blood glucose control of diabetic patients in Hospital Region 4 : Ayutthaya province - Kumwong, Kamolwan; Ewers, Thanyaporn; Buathed, Decha (Journal of Medical and Public Health Region 4, 2024)
Patients with good blood sugar control (target 40%) had 27.10% with the least control in fiscal year 2019 in the 4th health region for Phra Nakhon Si Ayutthaya Province. This study aims to study the process, coverage, completeness, problems, obstacles, and solutions for registering diabetic patients who can control their blood sugar levels. The qualitative mixed-methods study format is to collect data by discussing group processes. A semi-structured interview was used. Personnel working in chronic non-communicable disease clinics of the Tharuea Hospital Health Service Network Quantitative data were collected using a diabetic patient record form. The results of the study found that when diagnosed as a diabetic patient, they would follow up with a blood test to check the blood sugar level with FBS. If the blood sugar level with FBS was 145 mg/dl, they would follow up next time if FBS was 145 mg/dl three or more times in a row. underwent treatment with behavior modification. And monitor blood sugar levels every 3 months. The doctor will send for an HbA1c test if it doesn't improve. Registration coverage was found to be 39.28 percent, with 88.60 percent completeness. Patients who received follow-up checks were able to control their blood sugar levels. 7.84% Data problems found that medical personnel responsible for entering ICD-10 codes did not know the codes for tracking. Therefore, it is necessary to decide to code as a diabetic patient. As a result, the data contains more diabetic patients than exists. and the diagnosis cannot be removed. Therefore, information system management should review goals and put them to good use using a participatory development process, namely policy formulation. Develop personnel potential. Provide opportunities for personnel to participate and promote the use of technology in recording diabetic patient information.